Mobilisasi Sumber Daya Gerakan Women, Life, Freedom dalam Resistensi Hukum Wajib Jilbab di Iran Tahun 2022 - Luthfina Amalia Royani; Linda Dwi Eriyanti; Muhammad Iqbal (Doh Gisin, 2025)
The Women, Life, Freedom Movement represents a feminist resistance against mandatory hijab laws in Iran, advocating for women’s rights and individual freedom of choice. This study aims to analyze how the movement utilizes resources in its struggle to achieve its objectives. Employing a qualitative approach with a literature study, the analysis is conducted through the perspectives of liberal feminism and resource mobilization theory. The results indicate that the success of the #WomenLifeFreedom movement is influenced by the effective utilization of resource opportunities, the strength of solidarity, and the narrative depth achieved through digital media. Social media has become a crucial tool for disseminating the movement’s ideology and organizing member participation. Despite facing pressure from the Iranian regime, the Women, Life, Freedom Movement persists through the support of local and global feminist groups, as well as effective resource mobilization strategies. This study underscores that access to the right resources is a vital factor in the success of social movements and in challenging repressive government systems.